Employer Assessment Relevance to Attitudes and Soft-Skills on Accounting Internship: Does It Influence the Student’s Performance? - Bedah AHMAD; Nadiah ABD HAMİD; Zarinah ABDUL RASİT; Norazian HUSSİN (Communications of International Proceedings, 2021)
The employability of accounting graduates has been an issue debated among academicians and industries worldwide. Potential employers have also raised concerns that university graduates seem to possess sufficient technical knowledge, but somehow, they lack the required soft skills such as communication and analytical thinking. Nevertheless, such claims have remained as disputes whether or not the assertions are reflecting the graduates. Since the internship program is part of an accounting degree requirement, this study provides an insight on the difference in attitude and soft skills acquired through internship programs between different types of employers; audit firms, and non-audit firms as well as between genders. The study also examines whether the attitudes and soft skills competencies acquired would influence the student’s subsequent academic performance. The student’s attitudes and soft skills were assessed using structured questionnaires on 224 accounting students of the Malaysian Public University who had undertaken their six-month internship period. The attitudes and soft skills assessed include general skill and motivation, job competency, interpersonal skill, responsibility, trainees’ knowledge and ability to communicate. The results provide evidence of an improvement in all the dimensions of attitudes and soft skills except for job competency when having an internship with the audit firms rather than the non-audit firms. Female students showed better performance in all the dimensions based on comparison between genders. The findings imply that the internship program is significantly influence student’s subsequent performance and able to prepare graduates with the necessary technical skills and soft skills for future accounting professionals.
Keywords: Employer’s Assessment; Student’s Attitude and Soft Skills; Accounting Internship; Student’s Performance